Amine-binding properties of salivary yellow-related proteins in phlebotomine sand flies. (December 2019) - Sumova, Petra; Sima, Michal; Kalouskova, Barbora; Polanska, Nikola; Vanek, Ondrej; Oliveira, Fabiano; Valenzuela, Jesus G.; Volf, Petr
Abstract: The amine-binding properties of sand fly salivary yellow-related proteins (YRPs) were described only in Lutzomyia longipalpis sand flies. Here, we experimentally confirmed the kratagonist function of YRPs in the genus Phlebotomus . We utilized microscale thermophoresis technique to determine the amine-binding properties of YRPs in saliva of Phlebotomus perniciosus and P. orientalis, the Old-World vectors of visceral leishmaniases causative agents. Expressed and purified YRPs from three different sand fly species were tested for their interactions with various biogenic amines, including serotonin, histamine and catecholamines. Using the L. longipalpis YRP LJM11 as a control, we have demonstrated the comparability of the microscale thermophoresis method with conventional isothermal titration calorimetry described previously. By homology in silico modeling, we predicted the surface charge and both amino acids and hydrogen bonds of the amine-binding motifs to influence the binding affinities between closely related YRPs. All YRPs tested bound at least two biogenic amines, while the affinities differ both among and within species. Low affinity was observed for histamine. The salivary recombinant proteins rSP03B ( P. perniciosus ) and rPorASP4 ( P. orientalis ) showed high-affinity binding of serotonin, suggesting their capability to facilitate inhibition of the blood vessel contraction and platelet aggregation. Graphical abstract: Image 1 Highlights: Microscale thermophoresis (MST) is suitable to measure amine-binding properties of sand fly yellow-related proteins (YRPs). The amine-binding function has been experimentally verified for YRPs of genus Phlebotomus. All YRPs bind at least two biogenic amines, while the affinities differ both among and within species. High-affinity binding of serotonin by YRPs potentially facilitates counteracting platelet aggregation and vasoconstriction.